2015
DOI: 10.1038/nmat4360
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives for Rashba spin–orbit coupling

Abstract: In 1984, Bychkov and Rashba introduced a simple form of spin-orbit coupling to explain the peculiarities of electron spin resonance in two-dimensional semiconductors. Over the past 30 years, Rashba spin-orbit coupling has inspired a vast number of predictions, discoveries and innovative concepts far beyond semiconductors. The past decade has been particularly creative, with the realizations of manipulating spin orientation by moving electrons in space, controlling electron trajectories using spin as a steering… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
1,466
1
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,779 publications
(1,487 citation statements)
references
References 180 publications
9
1,466
1
11
Order By: Relevance
“…Also, the interaction in strained Ge QW has been identified as the cubic Rashba S-O interaction, due to quantum confinement in the heavy hole valence band only [56,57] The energy term arising from the Rashba interaction is cubic in k-space, and must be treated with a different analysis to the linear interaction in electron and light hole QW. The S-O interaction is an important component in future spintronic technologies, with applications in areas as diverse as spin transistors, quantum computing (S-O qubits), S-O torque, the spin Hall effect, chiral magnonics and to create band inversion for the formation of topologically insulating states to generate the quantum spin Hall effect [58]. The ubiquitous nature of this physical phenomena has led to the introduction of a new field of research, spin-orbitronics.…”
mentioning
confidence: 99%
“…Also, the interaction in strained Ge QW has been identified as the cubic Rashba S-O interaction, due to quantum confinement in the heavy hole valence band only [56,57] The energy term arising from the Rashba interaction is cubic in k-space, and must be treated with a different analysis to the linear interaction in electron and light hole QW. The S-O interaction is an important component in future spintronic technologies, with applications in areas as diverse as spin transistors, quantum computing (S-O qubits), S-O torque, the spin Hall effect, chiral magnonics and to create band inversion for the formation of topologically insulating states to generate the quantum spin Hall effect [58]. The ubiquitous nature of this physical phenomena has led to the introduction of a new field of research, spin-orbitronics.…”
mentioning
confidence: 99%
“…In particular, InAs and InSb nanowires are promising systems for the creation of helical states and as a host for Majorana fermions [11][12][13]. The fundamental reason behind these properties is the strong Rashba spin-orbit interaction (RSOI) in these materials [14].Recently we have found that RSOI is created by the electric field of the image charges that electrons induce on a nearby gate [15]. A sufficiently strong image-potential-induced spinorbit interaction (iSOI) leads to highly non-trivial effects such as the collective mode softening and subsequent loss of stability of the elementary excitations, which appear because of a positive feedback between the density of electrons and the iSOI magnitude.…”
mentioning
confidence: 99%
“…In particular, InAs and InSb nanowires are promising systems for the creation of helical states and as a host for Majorana fermions [11][12][13]. The fundamental reason behind these properties is the strong Rashba spin-orbit interaction (RSOI) in these materials [14].…”
mentioning
confidence: 99%
“…This behavior is a consequence of the pseudoone-dimensional character of the zero-point motion in the system brought about by the non-trivial topology of the occupied states in momentum space. This conclusion affects a large class of laboratory two-dimensional systems, specifically surfaces, interfaces and heterojunctions with Rashba spin-orbit interaction [4] and a variety of fewlayer systems [5]; a notable representative of the latter group is biased bilayer graphene [6]. The only other example of anomalous screening known to us is that of a three-dimensional electron gas in a very strong magnetic field [7].…”
mentioning
confidence: 99%
“…In the range of doping we are interested in, 0 µ 2 k 2 0 /2m, all the momentum states sandwiched between circles of inner radius k 1 = k 0 − 2mµ/ 2 and outer radius k 2 = k 0 + 2mµ/ 2 are occupied, and higher energy BR bands [10] play no role. While the dispersion law (1) adequately describes the Rashba materials [4] within the stated range of doping, for few-layer substances [5] its range of applicability is narrowed to the vicinity of its minimum k = k 0 . Moreover, for the BR electrons the spectral degeneracy is lifted by the spin-orbit interaction which may not be the case for few-layer materials [5] where spin and/or valley degeneracies may remain.…”
mentioning
confidence: 99%